First record of predation by the Andean white-eared opossum Didelphis pernigra on the red swamp crayfish Procambarus clarkii in Colombia - González-Ruiz, Yesid de los Ángeles; Pimiento-Ortega, Mabel Giovana; Herrera-Martínez, Yimy (Therya Notes, 2022)
The Virginia opossum (Didelphis virginiana) has been identified as a predator of the red swamp crayfish (Procambarus clarkii) in North America. In the regions where this crayfish has been introduced, other mammals have been identified that include it in their diet. The present paper is the first record of predation by D. pernigra, a species that is endemic to the Andean Mountain range, on the invasive exotic crayfish P. clarkii in Colombia. We carried out 100 m transects in a riverside forest in the middle basin of the Chicamocha River, Colombia. We collected feces and recorded tracks, and afterwards, obtained photographic records of individual opossums in the area. We weighed the feces, then dissolved them and separated them in Petri dishes. The tracks and the individuals photographed were identified using a specialized bibliography. We found structures in the feces that allowed the identification of 5 individuals of the species P. clarkii, an odonate, as well as Poaceae seeds. The tracks and the specimens photographed belong to the species D. pernigra, a species previously recorded in the region. The colonization and reproduction of P. clarkii in the area represents a new resource that the species D. pernigra has integrated into its diet. D. pernigra’s predation on P. clarkii may be related to the nocturnal behaviour of both species, which increases the probability of predation. It is likely that this South American species of the genus Didelphis may modify their diet if the invasion area of P. clarkii increases.